Anaerobic Digestion and Codigestion of Chlorella Vulgaris Microalgae Biomass with Wastewater Sludge and Dairy Manure for Biogas Production - Ammar, Saad H.; Khodhair, Sadiq Riyadh (Al-Khwarizmi Engineering Journal, 2017)
Abstract Anaerobic digestion process of organic materials is biochemical decomposition process done by two types of digestion bacteria in the absence of oxygen resulting in the biogas production, which is produced as a waste product of digestion. The first type of bacteria is known as acidogenic which converts organic waste to fatty acids. The second type of bacteria is called methane creators or methanogenic which transforms the fatty acids to biogas (CH4 and CO2). The considerable amounts of biodegradable constitutes such as carbohydrates, lipids and proteins present in the microalgae biomass make it a suitable substrate for the anaerobic digestion or even co-digested with other organic wastes. The present work investigated methane biogas production by anaerobic codigestion of microalgae, Chlorella vulgaris biomass with organic waste from several sources such as wastewater sludge and dairy manure waste in different proportions as an additional carbon supply to enhance anaerobic digestion and therefore biogas production. Six bottles, employed as batch biodigesters each of 1 liter capacity, were used for that purpose at moderate conditions (35±2 oC). The produced biogas volume was monitored daily along 35 days and the results showed that the daily and cumulative biogas production was increased 4.5 times and 3 times for the bottles with 66.67% microalgae compared with the bottles with wastewater sludge or dairy manure waste only, respectively. Keywords: Anaerobic codigestion, biogas; dairy manure, microalgae Chlorella Vulgaris, wastewater sludge.